Republic of Sierra Leone Public Expenditure and Financial Accountability : Performance Assessment Report 2010, Sub-National Governments (Local Councils) - Mulit Donor Budget Support Partners (World Bank, Washington, DC, 2013)
This Public Financial Management (PFM) Performance Assessment Report is based on the Public Expenditure and Financial Accountability (PEFA) PFM Performance Measurement Framework, Sub National Level, which includes a performance rating on 32 indicators covering the entire PFM cycle in Local Government, as in Sierra Leone, and assesses impact on budget goals. This assessment is intended to provide a comprehensive, integrated and candid assessment of Sierra Leone s PFM at the local council level, and to make recommendations for improving the local council PFM framework, institutional performance and capacity building.